Effect of AR42 in Primary Vestibular Schwannoma Cells and a Xenograft Model of Vestibular Schwannoma. Issue 6 (July 2022) - Misztal, Carly; Bracho, Olena; Bas, Esperanza; Estivill, Michael; Ivan, Michael E.; Morcos, Jacques; Bhatia, Rita; Telischi, Fred; Liu, Xue-Zhong; Gultekin, Sakir H.; Fernandez-Valle, Cristina; Dinh, Christine T.
Abstract : Hypothesis: AR42, a histone deacetylase (HDAC) inhibitor, reduces viability of primary vestibular schwannoma (VS) cells and delays tumor progression and hearing loss (HL) in a xenograft model of VS. Background: The impact of HDAC expression on AR42 response in primary VS cells is unknown, as well as the effects of AR42 on VS-associated HL and imbalance. Methods: Primary human VS cells (n = 7) were treated with AR42 (0–3.0 μM), and viability assays were conducted. Immunohistochemistry and western blotting for phosphorylated-HDAC2 (pHDAC2) were performed on tumor chunks. Pharmacokinetic studies were conducted in Fischer rats using mass spectrometry. Merlin-deficient Schwann cells were grafted onto cochleovestibular nerves of immunodeficient rats and treated with vehicle (n=7) or AR42 (25 mg/kg/day for 4weeks; n=12). Tumor bioluminescence imaging, auditory brainstem response (ABR), and rotarod tests were conducted to 6weeks. Final tumor weight and toxicities were measured. Results: AR42 caused dose-dependent reductions in viability of VS cells. Tumors with higher pHDAC2:HDAC2 ratios had greater reductions in viability with AR42. On pharmacokinetic studies, AR42 reached peak levels in nerve 24 hours after oral administration. Although AR42-treated rats demonstrated mean ABR threshold shifts 10 to 20 dB lower than controls, this did not persist nor reach significance. When compared to controls, AR42 did not affect tumor bioluminescence, tumor weight, and rotarod measurements. Conclusions: Response of primary VS cells to AR42 may be influenced by pHDAC2 expression in tumor. Although AR42 may delay HL in our xenograft model, it did not halt tumor growth or vestibular dysfunction. Further investigations are warranted to evaluate the AR42 effectiveness in NF2-associated VS.